Dynamic Vascular Pattern (DVP), a Quantification Tool for Contrast Enhanced Ultrasound - Cui, X. W.; Ignee, A.; Jedrzejczyk, M.; Dietrich, C. F. (Zeitschrift für Gastroenterologie, 2013)
Contrast-enhanced ultrasound (CEUS) is widely applied in tumour diagnosis, especially for focal liver lesions (FLL), due to its high sensitivity and specificity. According to the European Federation of Societies for Ultrasound in Medicine and Biology (EFSUMB) CEUS guidelines (2012) and non-liver guidelines (2011), the majority of tumours, regardless of location, show specific CEUS enhancement patterns that can distinguish benign from malignant lesions. However, even experienced clinicians evaluating FLL may find occasional irregularities in these patterns, due to particular FLL pathologies, that make a definitive diagnosis difficult. Hence, there is a need to train physicians to utilize contrast enhancement kinetics to aid in the correct interpretation of data from CEUS examinations in patients with divergent liver tumour pathologies. Here we report on a CEUS quantitation software, SonoLiver®, to verify and improve diagnostic accuracy in the characterization of suspicious liver lesions through the analysis of dynamic vascular patterns (DVP).
Keywords: Tumor; Hämangiom; Metastase